KARAKTERISTIK ARSITEKTUR MASJID TUA BUNGKU DI KELURAHAN MARSAOLEH - sulfandi nur; Sandy Suseno (SANGIA: Jurnal Penelitian Arkeologi, 2019)
This research aims to describes the descriptives (1).The characteristics of the architectures of ancient Bungku mosque,(2) The function of ancientBungku Mosque (3) The factors that influenced the Architecturecharacteristics ancient Bungku mosqueThis research uses the archaeological theory (the cultural history theory)with architectural approaches. The methods which have been used in this research is descriptive and qualitativealong with the reasoning of analytical descriptives by applying the three forms of analytical approaches which ismorphological, technological and stylistic analysis.The result of this research showed that ancient of BungkuMosque has the characteristics of the architect which can be seen from its dome at the top of the roof with thefive limasan roof styles wich is gets smaller to the top and have the five Islamic pillars and five time daily prayers.At the top of the dome there is Alif pole and inside the mosque there are four main pillars wich was designed withthe rectangles, has one main door, have the mihrab and pulpit, the space of the main room was used for the menas well as having the porch, the function of the mosque is the Jami mosque and the place to pray/recite. As forthe dome of the ancient of bungku mosque was influenced by the Islamic in Ternate, the stages of roof and thelotus flower decoration on the pulpit of the ancient of Bungku mosque was influencedby the styles of the mosquein the Ternate’s sultanate.